Mapping cognitive capitalism to mitigate the urban museification - García, Felipe Luis (2019)
The aim of the article is to map the changes undergone by cognitive capitalism to gain an understanding of the contemporary city. First, the article takes a conceptual approach in order to perceive current urban cultural problematics. At the same time, it seeks to reconstruct the genealogy of leisure tourism, analyzing its transformations and exploring the complex framework of enhancement promoted to museify contemporary cities, establishing to this end a fundamental nexus between cultural consumption and the tourist industry. Finally, the article promotes a critical and reflexive approach to formulating possible alternatives to mitigate urban museification.